Análise da expressão gênica das peroxirredoxinas em pacientes talassêmicos e com anemia falciforme - Romanello, Karen Simone (2013)
Reactive Oxygen Species (ROS) are generated by the incomplete reduction of oxygen during metabolic processes, exposure to external agents and as a secondary response to several diseases and when in excess, can cause injury to tissues and cells. During the evolution process, cells have developed several antioxidant mechanisms. One of such mechanisms encompasses the peroxiredoxins (PRDXs), which are highlighted for their abundance and high reactivity with their substrates. In humans, six different PRDXs have been described as located in different cellular compartments. In erythrocytes, PRDXs, particularly PRDX2, is the third most abundant protein, indicating its possible role in the cell development and their maintenance. However, there are few studies connecting these proteins to erythroid diseases, especially in hemolytic anemias, that have a high ROS production, such as beta thalassemia and sickle cell disease (SCD). This study evaluated the role of PRDXs in reticulocytes of patients with the diseases described above, compared to reticulocytes of health blood donors, using Real Time PCR and proteins will be analyzed by Western blot. Our results showed that the levels of transcript and PRDX1 protein were increased in BT patients and decreased in SCD. The PRDX2 transcript showed no differences in both diseases but in western blot analysis a decrease in PRDX2 protein was observed in SCD, indicating a possible pos transcription regulation process for this gene in SCD. The levels of PRDX5 transcript did not present difference in any of the diseases. A reduction in mRNA and protein levels for PRDX6 was observed in BT and SCD patients. Besides its action in the detoxification of ROS, PRDX6 acts also as a phospholipase A2 regulating the phospholipid turnover at the cell membrane. The decrease of this enzyme found in both patients could indicate that the cell membrane of the erythroid cells were not renovated leading to hemolysis observed in these patients. This is the first study correlating gene expression of peroxiredoxins in these hemolytic anemias The results could contribute in better understand the role of these protein and in a identification of new targets that could help in the management of diseases and improve the survival of these patients.